Students’ Experience on Task Repetition in Collaborative Online Writing of Video-Based Task - Zur, Sarjaniah; Halim, Abdul; Alawiyah, Siti; Safei, Nur Hasanah; Atikah, Dewi; Nurfaidah, Sitti (Institut Agama Islam Negeri Kendari, 2023)
This qualitative study aimed to explore students’ experience on task repetition in collaborative online writing of video-based task. The data were collected through semi-structured interviews of fifteen English students in the third semester at an Islamic higher institution in Southeast Sulawesi who have carried out task repetition in collaborative online writing of video-based task. The researcher conducted a semi-structured interview by telephone and the interview process was recorded to make it easier for the researcher to transcribe the results of the interviews. Using thematic analysis, the finding revealed that most of the participants tend to have positive experience when carrying out task repetition in collaborative online writing of video-based task. Moreover, numerous challenges faced by students in doing task repetition were also presented in the finding of this study.